Effect of giving viterna plus supplements at different doses in feed on growth, survival rate, and feed conversion ratio of milkfish (Chanos chanos) seeds - Melanie, Kavinta; Zilfira, Zyudika; Akbar, Said Ali (Arwana: Jurnal Ilmiah Program Studi Perairan, 2023)
One of the viterna plus supplements, which are simple to digest and can improve the effectiveness and efficiency of fish digestion, is a supplement that adds nutritional value for growth. The goal of this study was to ascertain how adding viterna plus supplements to the feed at various doses would affect the growth of milkfish fry. With 5 treatments and 4 replications, the method used a non-factorial Completely Randomized Design (CRD). Absolute length, weight gain, feed conversion ratio, and specific growth rate all demonstrated a significant effect in the ANOVA test results (P 0.05). However, there was a significant effect on survival (P> 0.05). The best absolute growth in weight and length was demonstrated by a dose of 20 ml/kg in feed, or 0.59 gr and 1.77 cm, respectively. With a feed conversion ratio of 1.10, the specific growth rate at this dose was 1.47% per day. In addition, a dose of 15 ml/kg of feed resulted in the best survival at P3 of 94.2%. Water quality still falls within the expected range. The growth of milkfish fry can be supported by the addition of viterna plus supplements at a dose of 20 ml/kg of feed.